Non-surgical management of rectal cancer. Series of 68 cases, long follow up in two leading centres in Argentina. Issue 11 (November 2016) - Sanchez Loria, Fernando; Iseas, Soledad; O'Connor, Juan Manuel; Pairola, Alejandro; Chacon, Matias; Mendez, Guillermo; Coraglio, Mariana; Mariani, Javier; Dieguez, Adriana; Roca, Enrique; Huertas, Eduardo
Abstract: Background: The non-surgical management in a selected group of rectal cancer patients has shown promising results with adequate follow up. Aims: describing the results of the non-surgical management in patients with complete clinical response, with a close follow up. Methods: Between 2006 and 2015, patients with rectal cancer, stages I-III, without metastasis, treated with neoadjuvant CRT/CT, who had clinical complete response were included. CCR was defined through digital palpation, endoscopy-based criteria and MRI. Follow up was set according to institutional guidelines. Results: 68 patients were included. Initial stage was assessed with MRI in 55/68 pts and EUS 11/68. Considering the recurrence risk factors 57.6% (29/68) were T2-3ab N0, 3.3% (2/68) were T4N0, 29% (20/68) were T3-4 N1-2, with 39.7% with positive MRC. Mean distance to the anal margin was 3 cm. Chemoradiation included radiotherapy at 50.4 cGy, and concurrent capecitabine. In 22% a fluoropirimidine and oxaliplatin-based schema was used as induction therapy. Median follow up was 37.5 months and response assessment time 9 weeks (5–19). Eleven patients recurred, 6 endoluminally, 3 developed mesorectal recurrence, and two distant failure. Five years DFS and OS were 76.3% and 93.8%. Conclusions: conservative management was feasible with close follow up in leading cancer centres. In this series, DFS and OS were comparable to the data already reported in the literature.